Peningkatan Hasil Belajar Bahasa Arab Peserta Didik Melalui Penerapan Teknik Think, Pair, Share Di Taman Tahfidz Ar-Rahman Gunung Sindur Bogor - Muhammad Dhiya; Siskha Putri Sayekti (Mutiara: Multidiciplinary Scientifict Journal, 2023)
The purpose of this study was to determine the improvement of Arabic language learning outcomes by applying the Think, Pair, Share (TPS) technique. This research is a type of classroom action research with the Kemmis & McTaggart model. The research subject which is the source of data collection is Ar-Rahman Tahfidz Park in Gunung Sindur, Bogor Regency. The results showed two things; (1) there was no significant increase in the use of the TPS technique with learning outcomes; (2) despite the insignificance, there were learning outcomes that increased with the continuous use of the TPS technique.